Primary optic nerve sheath meningiomas: a follow-up study - Schick, Uta; Jung, Carla Sabine; Haßler, Werner (Central European neurosurgery, 2010)
The management of optic nerve sheath meningiomas (ONSM) remains controversial, but includes surgery, radiotherapy and plain observation. We present a follow-up study and treatment modalities based on our classification system.
Gesehen am 06.06.2023